Cerebrovascular Insult as Presenting Symptom of Neurofibromatosis Type 2 in Children, Adolescents, and Young Adults - Gugel, Isabel; Mautner, Victor-Felix; Kluwe, Lan; Tatagiba, Marcos Soares; Schuhmann, Martin Ulrich (Frontiers in Neurology, 2018)
Background and Purpose: Neurofibromatosis Type 2 (NF2) is an autosomal-dominant tumor-prone disorder characterized by the manifestations of central nervous system lesions. However, the first clinical signs of disease are often non-tumorous. Cerebrovascular insults are known in NF2, however, not yet described as first symptom in young NF2 patients. Methods: Magnetic resonance image scans of 298 NF2 patients treated in our neurofibromatosis center in Tübingen from 2003 to 2017 were retrospectively evaluated focusing on presence of aneurysms and ischemic stroke. Clinical data were used to clarify whether or not ischemic stroke or aneurysm rupture were the first presentation of disease. Blood of the patients were subjected to genetic screening for constitutional NF2 mutations. Results: We identified 5 cases under age of 25 years with aneurysms or ischemic stroke. Among them three had ischemic strokes of the brain stem and one aneurysmal subarachnoid hemorrhage as the first symptom of the disease. Incidental finding of 2 intracranial aneurysm occurred in one patient. All aneurysms were clipped. Patients with ischemia suffered from dysarthria, gait disturbances, dizziness and hemiparesis. Residual signs of hemiparesis and dysarthria persisted in one patient. All others fully recovered from the cerebrovascular insult. Bilateral vestibular schwannomas and intracranial meningiomas were found in all 5 patients. Conclusions: A cerebrovascular insult in the vertebrobasilar territory may occur as first symptom of disease in young NF2 patients. The brain stem seems to be especially prone to ischemic stroke. Multicenter studies on large NF2 cohorts are needed to determine the prevalence and pattern of cerebrovascular insults and disease in NF2 patients.